Marketing analysis of the pharmaceutical market of antidiabetic drugs in Ukraine - A. O. Savych; B. V. Pavliuk (Zaporozhye State Medical University, 2022)
Diabetes mellitus is an important public health issue. Statistics show a rapid growth in the number of patients each year, which increases the financial burden on the state's economy. Therefore, systematic marketing monitoring of the pharmaceutical market of drugs for diabetes is appropriate and permanently relevant. The aim of the research was to study the pharmaceutical market of antidiabetic drugs in Ukraine as of the first quarter of 2022. Materials and methods. The nomenclature range of drugs was analyzed in accordance with the State Register and the Anatomical-Therapeutic-Chemical Classification. The objects of research were information on synthetic hypoglycemic drugs registered in Ukraine, as well as herbal medicines belonging to the category A10 "Antidiabetic drugs". Analytical and comparative methods, as well as marketing analysis and generalization of information were applied. Results. The structure of the pharmaceutical market of medicines from category A10 "Antidiabetic drugs" is formed by mono-drugs, their share is 84.2 %, while combined drugs make 12.9 %, and only 2.9 % belongs to medicinal plant raw materials and their mixtures. Among mono-drugs, the most numerous by the number of trade names is the group of sulfonylureas and biguanides, the percentage of which is 33.9 %. The pharmaceutical market of antidiabetic drugs in Ukraine is import-dependent, as the share of foreign medicines from 24 importing countries is 59.3 %. Domestic manufacturers of drugs for type 2 diabetes are 10 pharmaceutical companies, among which production output is dominated by JSC "Farmak" - 31.9 %. Preparations based on medicinal plant raw materials are manufactured by PJSC "Liktravy" and PJSC Pharmaceutical Factory "Viola" in the form of mixtures and medicinal raw materials. Conclusions. The nomenclature ranges of drugs, which according to the ATC classification belong to the category A10 "Antidiabetic drugs", are analyzed and the structure of the segment is described. The range of herbal antidiabetic drugs has been studied and their share in the structure of the pharmaceutical market of Ukraine has been determined. The prevalence of foreign-made drugs over domestic ones has been established.